2022
DOI: 10.1007/s11274-022-03449-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxalic acid degradation in wood-rotting fungi. Searching for a new source of oxalate oxidase

Abstract: Oxalate oxidase (EC 1.2.3.4) is an oxalate-decomposing enzyme predominantly found in plants but also described in basidiomycete fungi. In this study, we investigated 23 fungi to determine their capability of oxalic acid degradation. After analyzing their secretomes for the products of the oxalic acid-degrading enzyme activity, three groups were distinguished among the fungi studied. The first group comprised nine fungi classified as oxalate oxidase producers, as their secretome pattern revealed an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Furthermore, Trametes strains secrete extracellular fatty acid droplets 49 and corrode apatite under glucose-limited conditions 50 . Graz et al 2023 confirmed the oxalic acid-degrading activity of Trametes and Laetiporus 51 . Oxalic acid is commonly secreted by the majority of fungi during the wood decay process, and it is linked with the ability to chelate metals 51 , 52 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, Trametes strains secrete extracellular fatty acid droplets 49 and corrode apatite under glucose-limited conditions 50 . Graz et al 2023 confirmed the oxalic acid-degrading activity of Trametes and Laetiporus 51 . Oxalic acid is commonly secreted by the majority of fungi during the wood decay process, and it is linked with the ability to chelate metals 51 , 52 .…”
Section: Discussionmentioning
confidence: 95%
“…Graz et al 2023 confirmed the oxalic acid-degrading activity of Trametes and Laetiporus 51 . Oxalic acid is commonly secreted by the majority of fungi during the wood decay process, and it is linked with the ability to chelate metals 51 , 52 . The endophytic fungi Sarocladium and Penicillium were enriched in the biofilms according to Deseq2.…”
Section: Discussionmentioning
confidence: 95%